Two New Species of Begonia (Begoniaceae, Section Petermannia) from Mount Sidole, Central Sulawesi, Indonesia - Dayanti, Eka P.; Pitopang, Ramadanil; Ardi, Wisnu H.; Thomas, Daniel C. (Phytotaxa, 2020)
Begonia sidolensis and Begonia rolandfadlii from Gunung Sidole (Parigi Moutong Regency, Central Sulawesi, Indonesia) are proposed as new species. Detailed descriptions and photo plates of both species are provided. Both species are provisionally assessed as belonging to the Vulnerable IUCN category.